Deposition rates of viruses and bacteria above the atmospheric boundary layer - Reche, Isabel; D’Orta, Gaetano; Mladenov, Natalie; Winget, Danielle M.; Suttle, Curtis A. (The ISME Journal, 2018)
Aerosolization of soil-dust and organic aggregates in sea spray facilitates the long-range transport of bacteria, and likely viruses across the free atmosphere. Although long-distance transport occurs, there are many uncertainties associated with their deposition rates. Here, we demonstrate that even in pristine environments, above the atmospheric boundary layer, the downward flux of viruses ranged from 0.26 × 10 9 to >7 × 10 9 m −2 per day. These deposition rates were 9–461 times greater than the rates for bacteria, which ranged from 0.3 × 10 7 to >8 × 10 7 m −2 per day. The highest relative deposition rates for viruses were associated with atmospheric transport from marine rather than terrestrial sources. Deposition rates of bacteria were significantly higher during rain events and Saharan dust intrusions, whereas, rainfall did not significantly influence virus deposition. Virus deposition rates were positively correlated with organic aerosols <0.7 μm, whereas, bacteria were primarily associated with organic aerosols >0.7 μm, implying that viruses could have longer residence times in the atmosphere and, consequently, will be dispersed further. These results provide an explanation for enigmatic observations that viruses with very high genetic identity can be found in very distant and different environments.